Structure, IR Spectrum and UV-Induced Photochemistry of a Pyridyl-Substituted 1,3,4-Oxadiazole-Thione in Ar Matrix and Intermolecular Interactions in the Neat Crystalline Phase - Sidir, Isa; Lopes, Susy; Paixao, Jose Antonio; Nikitin, Timur; Jesus, Antonio Jorge Lopes; FAUSTO, RUI (Elsevier Science SA, 2025)
The structure, infrared (IR) spectrum and UV-induced (lambda > 235 nm) photochemistry of 5-(4-pyridyl)-1,3,4-oxadiazole-2(3H)-thione (abbreviated as POT) isolated in a low-temperature argon matrix, at 15 K, were thoroughly investigated. Interpretation of the experimental spectrum was assisted by theoretical calculations undertaken at the DFT(B3LYP)/6-311++G(d,p) level of theory. In the gas phase (and in the cryogenic matrix) the molecule of the compound was found to adopt the thione-amine tautomeric form, where NH is vicinal to CS, i.e., the same tautomeric form previously observed in the neat crystalline form of the compound. Upon sublimation and subsequent deposition into the argon matrix, the compound underwent minor, yet detectable, conversion into other species. These photoproducts were identical to those formed upon in situ broadband UV irradiation (lambda > 235 nm) of the matrix-isolated compound. Two different reaction pathways were identified: the first (minor) being the CO open-ring reaction leading to the formation of an isocyanate derivative, and the second (major) corresponding to the OCS extrusion generating allenic and propargylic type bond-shift isomeric nitrilimines. The carbodiimide and cyanamide resulting from subsequent rearrangement of the nitrilimines were also observed both in the as-deposited matrix (as a result of the thermally-induced chemistry taking place during sublimation of the compound) and after in situ UV-irradiation of the matrix. The nitrilimines were only captured during the photolysis experiments and were not observed in the spectra of the initially deposited matrix, because they quickly converted to the more stable carbodiimide and cyanamide isomeric forms during matrix deposition. Coupled-cluster calculations with single and double excitations [CCSD/6-311++G(d,p)] were also performed to further characterize the nitrilimines, revealing that the allenic form is slightly more stable than the propargylic one, in agreement with the spectroscopic data. The IR and Raman spectra of the neat crystalline compound were also analyzed in the temperature range of -140 to 220 degrees C, and the dominant intermolecular interactions in the crystal were elucidated using CrystalExplorer-based analysis of Hirshfeld surfaces and interaction energies. Overall, this study contributes to understanding of the structure, spectroscopy and chemical reactivity of oxadiazoles.
Keywords: Hirshfeld Surface; Infrared Spectroscopy; Matrix Isolation; Nitrilimine Bond-shift Isomers; Oxadiazoles; Photochemistry; Quantum Chemical Calculations; Raman Spectroscopy; Thermal Degradation